Effect of Cystine in Alkaline CMP Slurry on Controlling the Galvanic Corrosion at Al-Co Interface. (30th September 2019) - Wang, Zhi; Sun, Ming; Niu, Xinhuan; Zhou, Jiakai; Cui, Yaqi; Yang, Chenghui; lu, Yanan; Huo, Zhaoqing; Zhou, Wanqing; Meng, Fanhao
Abstract : As the feature size of integrated circuit (IC) shrinks down to 28 nm and below, aluminum (Al) is considered to be one of the suitable gate materials, and cobalt (Co) is considered to be one of the suitable barrier materials. During chemical mechanical polishing (CMP) of the Al-Co gate, galvanic corrosion occurs when Al and Co with large open-circuit potential (Eocp ) difference contact each other in device structure and are exposed to conductive CMP slurry. In this paper, the adsorptive properties of the complex products formed by cystine and metal Al and Co were investigated. By means of potentiometric dynamic and static polarization measurements, impedance monitoring technology and adsorption model establishment, the complex products were adsorbed on the surface of Al and Co in physical and chemical form, which hindered the corrosion of Al and Co and achieved the goal of reducing their galvanic corrosion. The dynamic potential difference between Al and Co was reduced to 23 mV, and the static Ecorr difference was reduced to 30 mV with cystine concentration of 8 mM/L. The dynamic corrosion current (Icorr ) difference was 2.936 μA/cm 2, and the static Icorr difference was 0.835 μA/cm 2 .